TINGKAT KEPUASAN MASYARAKAT TERHADAP KINERJA KEPEMIMPINAN KEPALA DESA LALOW KECAMATAN LOLAK KABUPATEN BOLAANG MONGONDOW - Siwij, Devie S. R. (Jurnal Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2018)
The purpose of this research is 1). To find out whether Lalow Village Leadership Lolak District Bolaang Mongondow District shows the expectations of the community? 2). To know what priorities should the village head have in its leadership? To answer the purpose of this research, the researchers conducted research based on the method of Importance and Performance Analysis used to obtain information about the level of community satisfaction of a service by measuring the level of importance and level of implementation. The results of the research show that 1). The average performance assessment of village chief leadership is below the average expectation (Importance): 2.47 <3.6. 2). The performance of each leadership variable from the score of respondents assessment (conformity level) below 100% (68.7% <100%) which means it has not been satisfactory. From the results of research and data analysis can be concluded that publik expectations of the overall value of Importance Performance Analysis (IPA) indicates that the leadership in Lalow Village District Lolak Bolaang Mongondow District is less than community expectations. which is quite high against the leadership of the village head.Keywords: Leadership, Interests and Performance